Correlation between Reflection Coefficient, Dielectric Properties and Brix Level of Malaysian Oranges at Microwave Frequencies - Rafidah Rosman; Mohamad Ngasri Dimon; You Kok Yeow (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents sweetness degree (°Brix) prediction of the Malaysian oranges using microwave technique. Experimental measurement using monopole sensor and reflectometer was done in order to correlate the relationship between measured reflection coefficient, S11  of the orange and its sweetness level. Up to fifty orange samples were freshly plucked from local grower’s farm and tested. The unique design of the monopole sensor’s holder is made of nylon. The experiment test bed was set up based on the standard dimension of monopole sensor available in the market. The operating frequency is focusing on 2.2 GHz as it shows significant sensitivity for determining Malaysian local oranges sweetness level.